1923’ten 2023’e Türkiye Ekonomisi - Uluğ, Eyüp Emre; Doğan, İbrahim and Somuncu, Ahmet and Ayvaz, Erkam Emin and Aslan, Alper and Oralhan, Burcu and Akagündüz, Halit Kerem and Himmetoğlu, Salih and Yılmaz, Şaban Fatih and Demirel, Neslihan and Şanlıoğlu, Ömer and Bulut, Yasin and Kaya, Ali and Özlü, Osman (Academician Publishing Book DOI Portal, 2024)
-